The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1063/1.4753986
|View full text |Cite
|
Sign up to set email alerts
|

The structure of ionic aqueous solutions at interfaces: An intrinsic structure analysis

Abstract: We investigate the interfacial structure of ionic solutions consisting of alkali halide ions in water at concentrations in the range 0.2-1.0 molal and at 300 K. Combining molecular dynamics simulations of point charge ion models and a recently introduced computational approach that removes the averaging effect of interfacial capillary waves, we compute the intrinsic structure of the aqueous interface. The interfacial structure is more complex than previously inferred from the analysis of mean profiles. We find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
60
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 74 publications
(105 reference statements)
10
60
0
Order By: Relevance
“…Thus, the surfactant-like behavior of Li + adsorption observed in the LiI solution is also seen in the LiBr and LiCl solutions, albeit to a lesser extent, and decreasing in the order LiI > LiBr > LiCl. The surface enhancement of Li + ions that we observed in lithium halide solutions agrees qualitatively with the results of previously reported MD simulations of 0.2 molal (m) and 1.0 m LiCl solutions (35), as well as an 8.6 m LiBr solution (36). We cannot quantitatively compare the extents of adsorption because of differences in the definition of the interface used to calculate density profiles.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Thus, the surfactant-like behavior of Li + adsorption observed in the LiI solution is also seen in the LiBr and LiCl solutions, albeit to a lesser extent, and decreasing in the order LiI > LiBr > LiCl. The surface enhancement of Li + ions that we observed in lithium halide solutions agrees qualitatively with the results of previously reported MD simulations of 0.2 molal (m) and 1.0 m LiCl solutions (35), as well as an 8.6 m LiBr solution (36). We cannot quantitatively compare the extents of adsorption because of differences in the definition of the interface used to calculate density profiles.…”
Section: Resultssupporting
confidence: 73%
“…1C and the integrated area ratios in Fig. 1D provide direct experimental confirmation of the prediction, made on the basis of MD simulations (34)(35)(36), that Li + ions adsorb to the aqueous solution-air interface.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…49 Thus, our experimental results are consistent with the involvement of such extended networks in LR-SIE at air-liquid interfaces. [60][61][62][63][64][65][66] In summary, we demonstrated that the depth of the interfacial layers sampled in our experiments is controlled by nebulizer gas velocity ν G. We found that the larger, rather than the more polarizable, anions are systematically enriched in the thinner (nanoscopic air-liquid-air) films produced at higher gas velocities in all tested solvents (water, methanol, 2-propanol, and acetonitrile). Addition of third ions (beginning at sub-μM levels) specifically perturbs the I − /Br − ratio in water and methanol solutions but has no effect in acetonitrile or 2-propanol.…”
Section: Resultsmentioning
confidence: 77%
“…The interfacial potential predicted by classical simulations can be, locally, much stronger, reaching values of ∼ −2 V, as reported in recent computations using methods that remove the smoothing effect of the interfacial capillary waves. 20 The modification of the interfacial potential upon addition of salt has been considered too, showing a significant dependence with salt concentration.…”
mentioning
confidence: 99%